The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s40644-020-00378-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinicopathologic factors and FDG avidity in radioiodine-negative recurrent or metastatic differentiated thyroid carcinoma

Abstract: Background In this study, we investigated the relationship between clinicopathologic factors, BRAFV600E mutation status and [18F] F-fluoro-2-deoxyglucose (FDG) avidity in patients with radioiodine (RAI)-negative recurrent or metastatic differentiated thyroid cancer (DTC). Methods From 2015 to 2018 all patients with suspected recurrent or metastatic radioiodine-negative DTC patients who underwent FDG positron emission tomography/computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Several studies have investigated the role of BRAF-V600E mutations as prognostic markers and have shown a strong correlation with poor clinicopathological outcomes of PTC. In particular, a close association of BRAF mutation with extrathyroidal extension, lymph node metastasis, and advanced TNM stages III/IV of PTC, which are welldocumented risk factors associated with increased rates of recurrence and mortality of thyroid cancer, have been reported [42][43][44][45][46]. The role of the BRAF-V600E mutation as a poor prognostic factor has also been reported in low-risk intrathyroidal tumors [44].…”
Section: Braf Point Mutationsmentioning
confidence: 95%
“…Several studies have investigated the role of BRAF-V600E mutations as prognostic markers and have shown a strong correlation with poor clinicopathological outcomes of PTC. In particular, a close association of BRAF mutation with extrathyroidal extension, lymph node metastasis, and advanced TNM stages III/IV of PTC, which are welldocumented risk factors associated with increased rates of recurrence and mortality of thyroid cancer, have been reported [42][43][44][45][46]. The role of the BRAF-V600E mutation as a poor prognostic factor has also been reported in low-risk intrathyroidal tumors [44].…”
Section: Braf Point Mutationsmentioning
confidence: 95%
“…Refractory tumors have an enhanced expression of glucose transporters, such as GLUT1 [ 188 , 189 ]. This change is reflected in the occurrence of 18 FDG-PET avid-metastases and is associated with iodine refractoriness, aggressive disease, and poor outcome [ 170 , 190 , 191 ].…”
Section: Rai Refractorinessmentioning
confidence: 99%
“…In our research, we also focused on whether extrathyroid invasion could lead to RAIR-DTC. Ha's study suggested that aggressive histopathologic subtypes were significantly associated with the recurrent or metastatic lesions in RAI-negative DTC (35). Robertson et al (36) conducted a multivariate analysis of 231 patients with thyroid cancer and found that lymphadenopathy was the only important risk factor for recurrence (p<0.001), and the presence of extrathyroid invasion (p=0.013) leaded to high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we also focused on whether extrathyroid invasion could lead to RAIR-DTC. Ha’s study suggested that aggressive histopathologic subtypes were significantly associated with the recurrent or metastatic lesions in RAI-negative DTC ( 35 ). Robertson et al.…”
Section: Discussionmentioning
confidence: 99%